Trends in the development of transport logistics in Ukraine (Economics and region, 2024)
The article provides an analysis of the key aspects of Ukraine's logistics system. It reviews the historical development of the country's transportation logistics and traces its dynamics. The challenges and opportunities affecting the development of the logistics sector are discussed. Emphasis is placed on the digitization of these processes. It is noted that, under current conditions, military logistics becomes of particular importance. The contemporary state of the industry, characterized by infrastructure development, integration of new technologies, yet facing challenges caused by infrastructural limitations, regulatory barriers, and the impact of military conflicts, is examined. Emphasis is made on the reasons that hinder the acceleration of the development of logistic processes in Ukraine. The prospects of the industry include further modernization, digitization, and integration with global logistics networks, requiring the attraction of investments and international cooperation. The article stresses the importance of logistics for economic growth and Ukraine's integration into the global economy, offering recommendations for further development of the sector, specifically: – Focus on the expansion and modernization of the road network, railways, and port facilities, including through private investments and international financial support; – Minimizing bureaucracy in the logistics sector, simplifying customs procedures, and creating more transparent conditions for business; – Special attention should be given to enhancing the security of transport routes, particularly through the development of monitoring systems and the implementation of modern security technologies; – The application of cutting-edge technologies and automated management systems can significantly improve the efficiency of logistics operations; – The development of bilateral and multilateral agreements with other countries and international organizations will facilitate the opening of new markets and strengthen Ukraine's integration into the global logistics system; – An important aspect will be the integration of environmental standards and practices into logistics processes, aimed at reducing the carbon footprint and enhancing the sector's environmental sustainability.
Keywords: logistics; transportation; analysis; logistic processes; development trends